2015
DOI: 10.1111/idh.12174
|View full text |Cite
|
Sign up to set email alerts
|

European Fissure Sealant Guidelines: assessment using AGREE II

Abstract: Based on the AGREE II instrument, the results obtained show significant variation in the quality assessment of the three European Fissure Sealant Guidelines. Future studies should be carried out both to develop quality dental CPGs and to investigate effective ways of adopting them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Continued efforts in evaluating sealant and caries prevalence in school‐aged children are necessary to monitor the attainment of oral health benchmarks set by Healthy People 2020 objectives . Standardization of school‐based programme outcomes would allow a more efficient means to observe children's oral health . Seal America's Preventive Intervention guidelines were created for administrators of sealant programmes as a strategy to standardize these outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…Continued efforts in evaluating sealant and caries prevalence in school‐aged children are necessary to monitor the attainment of oral health benchmarks set by Healthy People 2020 objectives . Standardization of school‐based programme outcomes would allow a more efficient means to observe children's oral health . Seal America's Preventive Intervention guidelines were created for administrators of sealant programmes as a strategy to standardize these outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…As in the present analysis, they obtained good scores for domain 1 (scope and purpose) and very poor scores for domain 5 (applicability) [9]. San Martin-Galindo et al [10] used the AGREE II tool to evaluate three guidelines on the use of pit and fissure sealants for dental clinicians; scores for domain 6 (editorial independence) were lowest. In the present study, this domain score was the third lowest when the consensus guidelines were evaluated alone.…”
Section: Discussionmentioning
confidence: 70%
“…In dentistry, the evaluation of guidelines using guideline assessment tools is in its infancy stage with only a few published articles. [17][18][19][20][21] Arieta-Miranda et al, 17 in their study on the quality of currently available international orthodontic guidelines, reported significant variations and sub-optimal quality level of CPGs. The quality assessment of CPGs in the management of paediatric dental emergencies applicable to the COVID-19 pandemic was conducted by Tejani et al, using Appraisal of Guidelines Research and Evaluation II (AGREE II) tool.…”
Section: Dentists and Other Healthcare Professionals Need To Use High...mentioning
confidence: 99%
“…San Martin‐Galindo et al assessed the quality of European dental CPGs. The results revealed critical variations across CPG recommendations, and they suggested the development of high quality dental CPGs and to investigate their dissemination 21 …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation